THE INFLUENCE OF GREEN MARKETING AND CORPORATE SOCIAL RESPONSIBILITY PRACTICES ON CONSUMER PURCHASE INTENTION (STUDY CASE: STARBUCKS COFFEE) - Pricilia Sumarmo; Paulus Kindangen; Merinda H. Ch. Pandowo (Universitas Sam Ratulangi, 2023)
One way for consumers to know whether the products offered are green and environmentally friendly products is by doing green marketing. By applying green marketing as their strategy, they are helping to make the world became greener and safer for the future and up to some extent they are delivering their Corporate Social Responsibility (CSR) by producing their products in an environmentally friendly way for the welfare of the environment and for the customers as a whole. The purpose of this study is to evaluate the influence of Green Marketing and Corporate Social Responsibility Practices on Consumer Purchase Intention in Manado (Study Case: Starbucks Coffee). The data was collected through an online survey questionnaire using purposive sampling technique of 100 respondents and analysis technique used is Multiple Linear Regression Analysis by using SPSS software. The research show that there is a positive and significant influence between Green Marketing and Corporate Social Responsibility Practices on Consumer Purchase Intention. Keywords: green marketing, corporate social responsibility, consumer purchase intention